ANALISIS KRONOFARMAKOLOGI PENGGUNAAN PARACETAMOL PADA PASIEN COVID-19 DI RSUD DR. SOEDOMO TRENGGALEK - Prasetyawan, Fendy; Saristiana, Yuneka; Muslikh, Faisal Akhmal; Mildawati, Ratna; Oktadiana, Isma; Arifin, Chandra; Rofiq, Abd; Febriana, Laela; Besan, Emma jayanti; Fadel, Muhammad Nurul (Journal of Social Science and Multidisciplinary Analysis, 2024)
The global COVID-19 pandemic has presented complex challenges to global health. Dr. Soedomo Regional General Hospital in Trenggalek has actively engaged in managing COVID-19 patients. This study aims to analyze the chronopharmacology of paracetamol usage in COVID-19 patients at the hospital, focusing on the body's biological response to the drug at various time points within the 24-hour cycle. In the treatment of COVID-19, the use of paracetamol has become a primary strategy for addressing symptoms such as fever. However, it is crucial to understand how the timing of paracetamol administration can influence the body's response to the treatment. A chronopharmacological study involving 100 patients analyzed body temperature before and after therapy at three different times: 08:00 AM, 04:00 PM, and 10:00 PM. The results revealed a significant decrease in body temperature after therapy, particularly at 04:00 PM. These findings support the concept of "the right time, the right dose" in clinical practice. Analysis of the body's circadian rhythm emphasizes the need to consider the timing of drug administration to achieve optimal outcomes. Despite the limited sample size, this research provides a foundation for the development of more precise practical guidelines for administering paracetamol to COVID-19 patients.